I love you sun, I love you moon - Pandell, Karen; DePaola, Tomie, 1934-2020 (New York : G.P. Putnam's Sons, 1994)
Small children discover the world around them and declare their relationship to all the wonders in that world.
On board pages.
BR
Keywords: Nature stories; Ecology -- Fiction